(untitled) (Sains Humanika, 2024)
The increasing demand for skilled workers in the construction industry underscores the importance of effective and modern education. Traditional approaches employed in teaching brickwork courses often face several challenges that impact the learning process. However, the use of academic modules resembling textbooks in the teaching and learning process (T&L) is seen as less suitable in meeting the challenges of the 21st-century curriculum changes. Moreover, the use of static and non-interactive modules leads to reduced student interest and attention because the T&L experienced is less engaging and makes it difficult for students to understand topics due to minimal sensory use. Therefore, this study was conducted to identify the elements required in the development of a web-based learning platform for brickwork and the level of student understanding before and after learning using the web-based platform. The study design utilized was a quasi-experimental quantitative approach using pre and post-tests involving control and treatment groups. The instruments used were checklist forms and pre and post-tests. Respondents involved in this study consisted of experts in Educational Technology and first-year (semester 2) Malaysian Vocational Certificate (SVM) students from the Construction Technology course at a Vocational College. Data analysis in this study was descriptive and inferential statistics, including mean scores, frequency, Mann-Whitney U Test, and Wilcoxon T Test. The results showed a significant improvement in student performance after using the web-based learning platform for brickwork. Findings indicate that the development of the web-based learning platform in terms of interface display and interaction, content and instructional structure, and facilitation received high marks from experts. Essentially, the use of web-based learning for brickwork courses not only modernizes the educational approach but also optimizes accessibility, interactivity, and better prepares students for success in the construction industry.